Numerical Investigation of Lime Particle Motion in Steelmaking BOF Process - Xiao, Yongli; Tian, Yufeng; Wang, Qiang; Li, Guangqiang (JOM (1989), 2021)
The motion and distribution of lime particles in a basic oxygen furnace (BOF) is explored using the proposed 3D comprehensive numerical model taking into account the supersonic oxygen jet, bottom-blowing bubble, melt flow, temperature distribution, and lime particle movement. The gas/slag/metal three-phase flow and interface fluctuation are described using the volume of fluid approach. The two-way coupled Euler–Lagrange method is employed to evaluate the rising of bottom-blowing bubbles. In contrast, the one-way coupled Euler–Lagrange method is adopted to represent the motion of lime particles, which are shown to continuously descend under the effect of gravity after feeding on the top surface. Upon touching the molten slag, the particles first move towards the furnace wall, turning back from both sides, and then travel to the middle from both ends. The particles finally gradually disperse to the whole molten slag layer because of the large- and small-scale vortices.